Enantioselective N-heterocyclic carbene-catalyzed cascade reaction for the synthesis of pyrroloquinolines via N-H functionalization of indoles - Mukherjee, Subrata; Shee, Sayan; Poisson, Thomas; Besset, Tatiana; Biju, Akkattu T. (Organic letters, 2018)
Functionalization of the indole N-H bond for enantioselective synthesis of biologically important pyrroloquinoline derivatives has been reported under oxidative N-heterocyclic carbene catalysis conditions. The interception of catalytically generated chiral alpha,beta-unsaturated acylazoliums with the indole derivatives proceeds in an aza-Michael/Michael/lactonization sequence to deliver the pyrroloquinoline derivatives in good yields, diastereoselectivities, and enantioselectivities. The simultaneous enhancement of reactivity and selectivity observed in polar aprotic solvents is noteworthy.

Enantioselective synthesis of tricyclic beta-lactones by NHC-catalyzed desymmetrization of cyclic 1,3-diketones - Shee, Sayan; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2020)
The NHC-catalyzed desymmetrization of cyclic-1,3-diketones allowing the enantioselective construction of tricyclic beta-lactones with five contiguous stereocenters, including two quaternary stereocenters, has been developed. The mild and operationally simple addition of a-bromoenals to cyclopentane-1,3-diketone derivatives proceeds via the initial formation of chiral alpha,beta-unsaturated acylazolium intermediates and culminates in a cascade reaction, following the Michael-aldol-Iactonization pathway to deliver the beta-lactone derivatives in moderate to good yields and excellent selectivity.

Enantioselective synthesis of 5,6-dihydroindolizines by N-heterocyclic carbene (NHC)-catalyzed core-structure-inspired strategy of azolium-enolate cascade - Ghosh, Arghya; Shee, Sayan; Barik, Shilpa; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2021)
The core-structure motivated design has allowed the enantioselective synthesis of 5,6-dihydroindolizines via N-heterocyclic carbene (NHC) catalysis. The NHC-catalyzed reaction of alpha,beta-unsaturated aldehydes with the suitably substituted pyrrole derivatives proceed via the initial generation of alpha,beta-unsaturated acylazoliums from enals, and enolates from pyrroles and the reaction culminated in an efficient cascade process involving the Michael-aldol-lactonization-decarboxylation sequence to afford the products in reasonable yields and high selectivities. The method is further extended to the construction of spirocyclic 5,6-dihydroindolizines.

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis

Dynamic kinetic resolution of gamma,gamma-disubstituted indole 2-carboxaldehydes via NHC-Lewis acid cooperative catalysis for the synthesis of tetracyclic epsilon-lactones - Balanna, Kuruva; Barik, Soumen; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (2022)
The ubiquity of epsilon-lactones in various biologically active compounds inspired the development of efficient and enantioselective routes to these target compounds. Described herein is the enantioselective synthesis of indole-fused epsilon-lactones by the N-heterocyclic carbene (NHC)-Lewis acid cooperative catalyzed dynamic kinetic resolution (DKR) of in situ generated gamma,gamma-disubstituted indole 2-carboxaldehydes. The Bi(OTf)(3)-catalyzed Friedel-Crafts reaction of indole-2-carboxaldehyde with 2-hydroxy phenyl p-quinone methides generates gamma,gamma-disubstituted indole 2-carboxaldehydes, which in the presence of NHC and Bi(OTf)(3) afforded the desired tetracyclic epsilon-lactones in up to 93% yield and >99 : 1 er. Moreover, preliminary studies on the mechanism of this formal [4 + 3] annulation are also provided.

Enantioselective synthesis of dihydrothiopyranones via NHC- catalyzed [3+3] annulation of 2-bromoenals with beta-oxodithioesters - Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2022)
The N-heterocyclic carbene (NHC)-organocata-lyzed [3 + 3] annulation of 2-bromoenals with fi-oxodithioesters resulting in the enantioselective synthesis of dihydrothiopyranones is presented. The chiral a,fi-unsaturated acylazoliums generated from 2-bromoenals and carbenes underwent smooth interception with the sulfur nucleophiles to furnish the sulfur heterocycles in satisfactory yields/selectivity. The regioselective formation of dihydrothiopyranones over the competing dihydropyranones is noteworthy.

NHC-catalyzed enantioselective synthesis of tetracyclic δ-lactones by (4+2) annulation of ortho-quinodimethanes with activated ketones - Sarkar, Deeptanu; Barik, Shilpa; Shee, Sayan; Gonnade, Rajesh G.; Biju, Akkattu T. (Organic Letters, 2023)
The N-heterocyclic carbene (NHC)-catalyzed generation of ortho-quinodimethanes (o-QDMs) from 9H-fluorene-1-carbaldehydes followed by the interception with activated ketones resulting in the enantioselective synthesis of tetracyclic delta-lactones is presented. High diastereoselectivity of products, remote C-(sp(3))-H functionalization, broad substrate scope, and mild reaction conditions are the notable features of the present (4 + 2) annulation.

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis